(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
This article basically tries to explain that opportunities are the key to success and how students can take advantage and learn new skills or to enhance existing ones. it is an understanding of the opportunities and using the strengths in the right way which in turn helps in achieving better. Higher education institutes provide platform to every individual, and can seek opportunities not just by looking at what he/she can do but rather he/she must be built in such way that they can recognise or analyse how he/she can use the resources or qualities that they already have within them or may build. This article is based on some case studies done on students of Amity University Haryana, India. And found how their personality changed during their degree at institute in terms of enhancing skills through opportunities. These students are always very positive in approach and were keen to learn and do something better for country.